Prognostic value of nutritional parameters in systolic heart failure with renal dysfunction. - Takahiro Doi; Takahiro Noto; Tomohiro Mita; Daigo Nagahara; Satoshi Yuda; Akiyoshi Hashimoto; Tomoaki Nakata; Kenichi Nakajima (PLoS ONE, 2022)
Although it is known that assessment and management of the nutritional status of patients are important for treatment of patients with heart failure (HF), there are currently no established indicators. Therefore, we investigated the effects of nutritional parameters as well as conventional parameters on the prognosis of HF patients. A total of 1954 consecutive HF patients with left ventricular ejection fraction (LVEF) less than 50% were enrolled in this study. Transthoracic echocardiography was performed and conventional parameters for HF patients and parameters to assess nutritional status were measured in all patients. Patients were followed up with a primary endpoint of lethal cardiac events (CEs) for 30.2 months. During the follow-up period, cardiac events were documented in 619 HF patients. The CEs group had a lower level of cholinesterase (201.5U/L vs 265.2U/L, P <0.0001), lower estimated GFR (35.2 ml/min/1.73m2 vs 50.3ml/min/1.73m2, P< 0.0001), and lower Geriatric Nutritional Risk Index (GNRI) (91.9 vs 100.0, P< 0.0001) than those in the non-CEs group. Serum cholinesterase, estimated GFR, and GNRI were identified as significant prognostic determinants in multivariate analysis. ROC analyses revealed cut-off values of serum cholinesterase, estimated GFR, and GNRI of 229U/L, 34.2 ml/min/1.73m2, and 95.6, respectively, for identifying high-risk HF patients. HF patients with serum cholinesterase< 229U/L, estimated GFR<34.3 ml/min/1.73m2, and GNRI< 95.6 had a significantly greater rate of CEs than that in the other patients (P<0.0001). Low serum cholinesterase and low GNRI can predict cardiac mortality risk in systolic HF patients with renal dysfunction.